Pengaruh Antara Implusive Attitude Dan Novelty-Fashion Attitude Dengan Pemanfaatan Rekomendasi Sosial Pengguna Aplikasi Traveloka Pada Generasi Z - Defira Ardita Meisthafa; Anisa Arizona Bandi; Tri Waluyo Prehantio (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. This study aimed to analyze the influence of impulsive attitude and novelty-fashion attitude on the use of social recommendations on the Traveloka app by Generation Z. A quantitative approach with a survey method was used to collect data through a questionnaire developed based on relevant theoretical frameworks. Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis technique was applied using the SmartPLS 3 software. Reliability tests showed that all variables have high reliability, allowing the data to be used for further analysis. Multiple linear regression analysis was employed to examine the effects of both independent variables on the dependent variable. The results indicated that both impulsive attitude and novelty-fashion attitude have a positive and significant effect on the utilization of social recommendations in the context of Traveloka platform usage, both simultaneously and partially. These findings contributed to the understanding of Generation Z's consumer behavior in decision-making based on social recommendations and provide strategic implications for the development of more effective digital marketing. Keywords: Social Recommendations, Traveloka, Consumer Psychographics